The geochemistry and palaeotectonic setting of lower proterozoic metavolcanic rocks and related intrusives in the Skellefte massive sulphide ore district, northern Sweden - Claesson, Lars-Åke (Luleå tekniska universitet, 1994)
Godkänd; 1994; 20080401 (ysko)